Description of a new species of Laccodytes Régimbart, 1895 (Coleoptera, Dytiscidae, Laccophilinae) from Cuba - Toledo, Mario; Megna, Yoandri S.; Alarie, Yves (Zootaxa, 2011)
Laccodytes cobrinae sp. n. is described from Cuba, which brings to 11 the number of species included in the Neotropical Laccophilinae genus Laccodytes Régimbart, 1895. Description and illustration of the new species are provided along with a discussion of its ecology and systematic position. The unexpected discovery of a new species in Cuba represents the first mention of Laccodytes in the Caribbean area, which extends considerably the distribution of the genus in the Neotropics. Such finding suggests that other species of Laccodytes could be found elsewhere in the Caribbean or Antilles as well as north of the Orinoco basin.